From above : an (Info)graphic novel - Panchaud, Martin, 1982- (Abrams ComicArts., 2025)
"This innovative, award-winning graphic novel uses the visual language of infographics to tell the story of Simon--an average teenager whose brush with a fortune teller sends him on a surreal adventure. From Above is an internationally acclaimed, groundbreaking graphic novel that tells its story from a bird's-eye view. Characters are depicted as colored circles in a graphic and strikingly designed visual approach reminiscent of Chris Ware's. Readers are encouraged to actively engage with the story as its relatively simple setup unfolds into a shocking and surreal adventure. Simon is an unpopular and awkward 14-year-old boy. Overweight, eager to please, and well-meaning, no matter how hard he tries, his lot in life is to be bullied by the neighborhood children and neglected by his absentminded parents. But one day everything changes for Simon when he does a favor for a fortune teller who rewards him by telling him the name of the winning horse at the Royal Ascot. Simon becomes an overnight millionaire when he bets his father's life savings on the winning horse. But as he returns home, he discovers that his mother is in a coma and his father has disappeared. Simon can't collect his winnings without finding his father, and he can't help his mother until he solves the mystery of her sudden condition. With time running out, can Simon change his fortune?"--Amazon.com.